Bio-Multifunctional Sponges Containing Alginate/Chitosan/Sargassum Polysaccharides Promote the Healing of Full-Thickness Wounds - Weiyan Quan; Puwang Li; Jinsong Wei; Yuwei Jiang; Yingye Liang; Weilin Zhang; Qizhou Chen; Kefeng Wu; Hui Luo; Qianqian Ouyang (Biomolecules, 2022)
Creation of bio-multifunctional wound dressings with potent hemostatic, antibacterial, anti-inflammatory, and angiogenesis features for bolstering the healing of full-thickness wounds is sought after for clinical applications. We created bio-multifunctional composite sponges by coupling alginate and chitosan with Sargassum pallidum polysaccharides through electrostatic interactions, calcium ion (Ca2+) crosslinking, and lyophilization. Alginate/chitosan (AC) sponges with different concentrations of Sargassum pallidum polysaccharides were obtained and termed AC, ACS—1%, ACS—2.5%, and ACS—5%. ACS—1% and ACS—2.5% sponges exhibited uniform porosity, high water vapor transmission rate, high water absorption, as well as good hemostatic and antibacterial abilities. ACS—2.5% sponges facilitated wound closure and promoted angiogenesis and re-epithelialization in the dermis. These data suggest that ACS sponges containing a certain amount of Sargassum pallidum polysaccharides could be employed for treatment of full-thickness skin wounds.